Oral Presentations Abstracts: EVERYDAY ETHICAL CHALLENGES AND INFORMAL ETHICS SUPPORT STRUCTURES OF MIGRANT CAREGIVERS IN OLDER ADULT CARE IN ENGLAND - BANDARA, Kumeri (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 This paper builds on anthropological fieldwork I conducted in 2019 while living for over two months with migrant caregivers of older adults in Epsom, England. Caregivers’ experiences resonated with existing literature on everyday ethical challenges in caregiving: navigating divergent perspectives on good care, negotiating professional disagreements on treatments, dealing with older adults’ verbal and physical abuse appropriately, and telling older adults ‘white lies’ to avoid mental distress. Caregivers also faced unique ethical challenges because of their migrant identities: dealing with racism, conscientious objecting of certain requests made by older adults, struggling with language when following training and defending themselves against exploitative managers, and carrying the burden of being a translator to fellow migrant colleagues. Based on insight into ethical challenges unique to migrant caregivers, this paper focuses on informal ethics support systems on which migrants relied ‒ an unexplored area in the literature on ethics support within social care ‒ and explores formal ethics support systems that could support migrant caregivers in the future. Existing literature shows that the UK in general lacks ethics support systems to help caregivers recognize and appropriately address ethical challenges. The literature goes on to explore kinds of formal ethics support systems that could address ethical challenges. However, the literature completely overlooks needs and challenges unique to migrant caregivers who increasingly constitute the older adult care workforce in the UK. Understanding everyday ethical challenges and informal support systems of migrant caregivers are important steps in ensuring wellbeing of caregivers, and thus, quality of care.